Evolutionary equilibrium in contests with stochastic participation: Entry, effort and overdissipation - Gu, Yiquan; Hehenkamp, Burkhard; Leininger, Wolfgang (Journal of Economic Behavior & Organization)
This paper examines the evolutionary stability of behaviour in contests where players’ participation can be stochastic. We find, for exogenously given participation probabilities, players exert more effort under the concept of a finite-population evolutionarily stable strategy (FPESS) than under Nash equilibrium (NE). We show that there is ex-ante overdissipation under FPESS for sufficiently large participation probabilities, if, and only if, the impact function is convex. With costly endogenous entry, players enter the contest with a higher probability and exert more effort under FPESS than under NE. Importantly, under endogenous entry, overdissipation can occur for all (Tullock) contest success functions, in particular those with concave impact functions.

Overcoming vulnerability: Channel design strategies to alleviate vulnerability perceptions in customer journeys - Wünderlich, Nancy V.; Hogreve, Jens; Chowdhury, Ilma Nur; Fleischer, Hannes; Mousavi, Sahar; Rötzmeier-Keuper, Julia; Sousa, Rui (Journal of Business Research)

Mapping Value in Business Markets: An Integrative Framework - Eggert, Andreas; Kleinaltenkamp, Michael; Kashyap, Vishal (Industrial Marketing Management)

Exploring the link between payment schemes and customer fraud: a mental accounting perspective - Garnefeld, Ina; Eggert, Andreas; Husemann-Kopetzky, Markus; Boehm, Eva (Journal of the Academy of Marketing Science)

Service Growth by Acquisition – An Event Study - Eggert, Andreas; Boehm, Eva; Akalan, Rodi; Gebauer, Heiko

Gift Purchases as Catalysts for Strengthening Customer–Brand Relationships - Eggert, Andreas; Steinhoff, Lena; Witte, Carina (Journal of Marketing)

Who trades cryptocurrencies, how do they trade it, and how do they perform? Evidence from brokerage accounts - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)
We investigate the demographic characteristics, trading patterns, and performance of 465.926 brokerage accounts with respect to cryptocurrency trading. We find that cryptocurrency trading became increasingly popular across individuals of all different groups of age, gender, and trading patterns. Yet, men are more likely to engage in cryptocurrency trading, trade more frequently, and more speculative, respectively. As a result, men realize lower returns. Furthermore, we find that investors vary their trading patterns across different asset classes.
Keywords: Cryptocurrencies Bitcoin Trading Investor returns Demographics

Are cryptocurrency traders pioneers or just risk-seekers? evidence from brokerage accounts - Pelster, Matthias; Breitmayer, Bastian; Hasso, Tim (Economics Letters)
Are cryptocurrency traders driven by a desire to invest in a new asset class to diversify their portfolio or are they merely seeking to increase their levels of risk? To answer this question, we use individual-level brokerage data and study their behavior in stock trading around the time they engage in their first cryptocurrency trade. We find that when engaging in cryptocurrency trading investors simultaneously increase their risk-seeking behavior in stock trading as they increase their trading intensity and use of leverage. The increase in risk-seeking in stocks is particularly pronounced when volatility in cryptocurrency returns is low, suggesting that their overall behavior is driven by excitement-seeking.
Keywords: cryptocurrencies; bitcoin; investor; risk-seeking

Essays on Drivers and Economic Outcomes of Online-Reviews - Gutt, Dominik

Bundling in a Distribution Channel with Retail Competition - Heinzel, Joachim Maria Josef
We analyze the incentives for retail bundling and the welfare effects of retail bundling in a decentralized distribution channel with two retailers and two monopolistic manufacturers. One manufacturer exclusively sells his good to one retailer, whereas the other manufacturer sells his good to both retailers. Thus, one retailer is a monopolist for one product but competes with the other retailer in the second product market. The two-product retailer has the option to bundle his goods or to sell them separately. We find that bundling aggravates the double marginalization problem for the bundling retailer. Nevertheless, when the retailers compete in prices, bundling can be more profitable than separate selling for the retailer as bundling softens the retail competition. The ultimate outcome depends on the manufacturers’ marginal costs. Given retail quantity competition, however, bundling is in no case the retailer’s best strategy. Furthermore, we show that profitable bundling reduces consumer and producer surplus in the equilibrium.
Keywords: retail bundling; leverage theory; double marginalization

All Things Considered? – Technology Design Decision-making Characteristics in Digital Startups - Bohn, Nicolai; Kundisch, Dennis (Proceedings of the 40th International Conference on Information Systems (ICIS))

Head over Feels? Differences in Online Rating Behavior for Utilitarian and Hedonic Service Aspects - Seutter, Janina; Neumann, Jürgen (Proceedings of the 40th International Conference on Information Systems (ICIS))

The App Updating Conundrum: Implications of Platform’s Rating Resetting on Developers’ Behavior - Gutt, Dominik; Neumann, Jürgen; Jabr, W.; Kundisch, Dennis (Proceedings of the 40th International Conference on Information Systems (ICIS))

Entwicklungsförderliche Gestaltung von Qualifizierungsbausteinen in der dualisierten Ausbildungsvorbereitung - Kremer, H.-Hugo; Frehe-Halliwell, Petra (BWP)

Eine Analyse ausbildungsvorbereitender Bildungsgänge - Kremer, H.-Hugo; Frehe-Halliwell, Petra (Potenzialorientierte Förderung in den Fachdidaktiken)

The Role of Prices Relative to Supplemental Benefits and Service Quality in Health Plan Choice - Bünnings, Christian; Schmitz, Hendrik; Tauchmann, Harald; Ziebarth, Nicolas R. (Journal of Risk and Insurance)

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (HCII 2019)
This paper explores Finnish, German and Swedish older adults’ perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults’ perception of the future use of welfare technology or care robots. A qualitative approach with focus group discussions was employed, followed by thematic analysis. The results are presented in four overall themes: the impact on daily life for older adults and professional caregivers, codes of practice and terms of use, dissemination of information and knowledge, and conditions for successful implementation. There were significant differences in the informants’ attitudes toward and knowledge about care robots. However, the informants’ attitudes appeared to change during the focus groups and in general, became more positive. Authentic needs, which care robots could support, refer to independence, safety and security, and the ability to manage or ease daily life or working life. The results suggest that older adults, after receiving relevant information, were open to the idea of being supported by care robots in their daily lives.
Keywords: Care robots; Older adults; Implementation; Information; Perceptions; Welfare technology

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

The Effect of Marker-less Augmented Reality on Task and Learning Performance - Sommerauer, Peter; Müller, Oliver; Maxim, Leonard; Østman, Nils (International Conference on Wirtschaftsinformatik)
Augmented Reality (AR) technologies have evolved rapidly over the last years, particularly with regard to user interfaces, input devices, and cameras used in mobile devices for object and gesture recognition. While early AR systems relied on pre-defined trigger images or QR code markers, modern AR applications leverage machine learning techniques to identify objects in their physical environments. So far, only few empirical studies have investigated AR's potential for supporting learning and task assistance using such marker-less AR. In order to address this research gap, we implemented an AR application (app)with the aim to analyze the effectiveness of marker-less AR applied in a mundane setting which can be used for on-the-job training and more formal educational settings. The results of our laboratory experiment show that while participants working with AR needed significantly more time to fulfill the given task, the participants who were supported by AR learned significantly more.

Fostering pre-service economics teachers´ reflection on their attitudes towards the discipline - Jenert, Tobias; Brahm , Taiga